The National Quality Awards (Part II): models for business competitiveness - García Pantigozo, Manuel (2000)
A modern businesses no longer enough for them implementing the Management Standards and ISO 9000 Asegurameinto d Quality, that are thousands that have this certification in the world. now need to differentiate competing to demonstrate what the best of the best are, for this decribes the model then reveals what ue has to make a modern enterprise to achieve competitiveness and why not compete for Prize and the quality of our country.